Evaluation of antioxidant properties in pickled lime and watermelon peels during storage / Zamlizawati Mohd Zain - Mohd Zain, Zamlizawati (Faculty of Applied Sciences, 2010)
Lime and watermelon peel were analyzed for antioxidant activity measured in ethanol extract. Total Phenolic Content used the Gallic acid as the standard, Total Flavanoid Content that used quercetin as standard, 1,1- diphenyl-2-picrylhydrazyl used the Ascorbic Acid as the standard and Ferric Reducing Ability of Plasma used the Trolox as the standard which method were used for determining antioxidant properties. The procedure gave results of single pickle where lime peel gave higher antioxidant compared to the watermelon peel. While, storage pickle gave result of decreasing antioxidant activity, where weekl > week2 > week3. Then the result of mixed pickled (cooked and fresh pickle), results that the cooked have higher antioxidant activity. Results from formulation, (80 LP: 20 WR >60 LP: 40 WR > 30 LP: 70 WR) showing that the first formulation (80LP: 20WR) have higher antioxidant activity.